Hidden Interests in the Origin of the Second World War - Salgado Defranc, José (2016)
In World War II, more than 60 million people died. The origin of this War is the subject of study of thisarticle. The origin of the war should’t be searched in the complex psychologies of nefarious personageslike Hitler, Goebels, Goering, Himmler. The true origins are linked to the deep financial interest ofAnglo-Saxon companies. The main objective was to seize the oil and mining wealth of the Soviet Union.These interests intersected with those of hegemonic powers that sought the destruction of the SovietUnion, Germany and the entire Continental Europe. In this case, the goal was for the United Statesto become the first world power. England benefited greatly from the weakening of its main rivals inContinental Europe: Germany and France. This article reveals the existence of dark characters such asHjalmar Schacht (President of the Reichbank and Minister of Economy of Hitler’s Government) andLord Montagu Norman (Governor of the Bank of England).